Kualitas post-thawing semen domba Merino dalam bahan pengencer berbasis susu skim-kuning telur yang ditambah isolat crude protein Tirosine Kinase - Widiantoro, Krisna; Madyawati, Sri Pantja; Sardjito, Trilas; Hernawati, Tatik; Triana, Indah Norma; Warsito, Sunaryo Hadi (Universitas Airlangga, 2021)
This study was conducted to determine the effect of crude protein tyrosine kinase (PTK) isolates supplementation into skim milk-egg yolk based diluent to maintain the quality of Merino ram spermatozoa. Four ejaculates of two Merino rams were divided into two groups for the control group (P0): Merino ram semen was diluted in skimmed milk-egg yolk based diluent, and the treatment group (P1): Merino ram semen was diluted in skim milk-egg yolk based diluent contained crude PTK 1,597 mg/ml diluent. All diluted semen was equilibrated for 2 hours at 5 °C and filled into 0.25 mL French straws. The filled straws were placed on steel racks (Cooltop, Minitube) held in liquid nitrogen vapour for 10 minutes at –140 °C, immersed immediately in liquid nitrogen at –196 °C, and stored for 48 hours for later assessment. Post-thawed semen samples were evaluated for spermatozoa motility, viability, and morphological abnormality. The results showed that the spermatozoa motility of fresh semen of Merino ram was 82.5 ± 2.89, which was qualified for freezing. The post-thawing spermatozoa motility, viability, and morphological abnormalities of Merino ram in the P1 group were 34.11 ± 3.26%, 38.00 ± 3.00%, and 12.89 ± 4.54%, respectively. It were higher (p <0.05) than the control group of 24.44 ± 2.9%, 26.67 ± 3.32%, and 21.11 ± 3.02%. It was concluded that the addition of crude PTK isolates of 1.597 mg/ml skim milk-egg yolk diluent improved the quality of post-thawed spermatozoa of Merino ram.